2020
DOI: 10.1002/aenm.202000567
|View full text |Cite
|
Sign up to set email alerts
|

Toward the Sustainable Lithium Metal Batteries with a New Electrolyte Solvation Chemistry

Abstract: graphite has been the most commercially successful anode material for LIBs due to its low material cost and reduction potential (≈0.05 V vs Li/Li + ). However, graphite anodes limit the enhancement of energy density and charging rate due to their low theoretical capacity (375 mAh g −1 ) and staged lithium (de) intercalation mechanism, making it difficult to meet the expectation of cutting-edge electronic devices. [5,6] Hence, the development of metallic lithium as an anode is attracting great attention because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(93 citation statements)
references
References 43 publications
(44 reference statements)
0
93
0
Order By: Relevance
“…However, the uncontrollable growth of Li dendrites and collapse of the solid electrolyte interphase (SEI) layer lead to low Coulombic efficiency (CE) and deteriorated cycling performance, which largely restrict the practical application of the Li metal anode (LMA) (7)(8)(9)(10)(11)(12)(13). Considerable efforts have been made to regulate the Li plating/ stripping behaviors for stable Li metal batteries, including developing functional electrolytes (14)(15)(16)(17)(18), constructing well-designed three-dimensional (3D) host structures (19)(20)(21)(22)(23)(24), and using artificial protection layers (25)(26)(27)(28)(29)(30). Despite much progress (31,32), it remains a challenge to explore LMA with stable cycling life over 500 cycles at practical current densities greater than 1 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…However, the uncontrollable growth of Li dendrites and collapse of the solid electrolyte interphase (SEI) layer lead to low Coulombic efficiency (CE) and deteriorated cycling performance, which largely restrict the practical application of the Li metal anode (LMA) (7)(8)(9)(10)(11)(12)(13). Considerable efforts have been made to regulate the Li plating/ stripping behaviors for stable Li metal batteries, including developing functional electrolytes (14)(15)(16)(17)(18), constructing well-designed three-dimensional (3D) host structures (19)(20)(21)(22)(23)(24), and using artificial protection layers (25)(26)(27)(28)(29)(30). Despite much progress (31,32), it remains a challenge to explore LMA with stable cycling life over 500 cycles at practical current densities greater than 1 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…Lithium-ion batteries (LIBs) with graphite anode have made a great impact on society, recognized by the Nobel Prize in Chemistry. [1] Following decades of commercialization, graphite copper fluoride, [11] magnesium nitrate, [12] tin trifluoromethanesulfonate, [13] and γ-butyrolactone, [14] lithium nitrate (LiNO 3 ) has been used to take part in the solvation sheath and produces Li + -conducting SEI layer. High-concentration electrolytes are also developed to improve the ratio of anions in the solvation sheath, leading to primarily inorganic SEI and better Li cyclability.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from LiNO 3 , some other N-containing additives can also be used to build nitrided SEI for Li metal electrodes. In this regard, Sun et al reported that Mg(NO 3 ) 2 can be dissolved in carbonate-based electrolyte as an additive 96. They suggested that Mg(NO 3 ) 2 can be dissolved directly as Mg 2+ and NO3 − …”
mentioning
confidence: 99%